2004
DOI: 10.1017/s1357321700002750
|View full text |Cite
|
Sign up to set email alerts
|

Longevity in the 21st Century

Abstract: The main objective of this paper is to offer a detailed analysis of mortality change in the United Kingdom at the beginning the 21st century. Starting from an exploration of 20th century mortality trends, focusing in particular on the 1990s, underlying forces driving trends in longevity are discussed. These include the 'cohort effect' and the 'ageing of mortality improvement'. International mortality statistics and trends are also analysed. The pace of medical advances is discussed, with specific focus on rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…These models do not allow for explicit quantification of uncertainty and the parameters are typically based on a mixture of recently observed trends and expert opinion [36]. This approach further systematically has underestimated the mortality improvements [9,30,35]. The observed fast increase of life expectancy, particularly for higher ages, in the last decades, the ongoing medical enhancement, and possible biological limits of lifespan raise the question of how to appropriately model future mortality.…”
Section: Introductionmentioning
confidence: 99%
“…These models do not allow for explicit quantification of uncertainty and the parameters are typically based on a mixture of recently observed trends and expert opinion [36]. This approach further systematically has underestimated the mortality improvements [9,30,35]. The observed fast increase of life expectancy, particularly for higher ages, in the last decades, the ongoing medical enhancement, and possible biological limits of lifespan raise the question of how to appropriately model future mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In Willets (2004) and Willets et al (2004) it is shown for example that cohort effect was first observed in the CMI assured lives dataset and was "propagated" to national population few years later.…”
Section: Pairwise Age-specific Cointegrationmentioning
confidence: 99%
“…The data that are used for these actuarial studies are provided by the UK life insurance industry. See Willets et al (2004) and Willets (2004), two recent mortality studies prepared under the auspices of the UK actuarial profession, and which provide good overviews of current mortality trends, for more information. A cohort effect can be seen in the bold figures shown in Table 3 and note also that, over calendar years, improvement rates have fallen at the younger ages, but have increased at the older ages.…”
Section: Mortality Improvementmentioning
confidence: 99%
“…A cohort effect can be seen in the bold figures shown in Table 3 and note also that, over calendar years, improvement rates have fallen at the younger ages, but have increased at the older ages. Willets et al (2004) discuss the reasons for this in detail.…”
Section: Mortality Improvementmentioning
confidence: 99%